Analisis Perbandingan Beban Kerja Mental Karyawan Organik dan Non Organik Menggunakan Metode NASA TLX dan Diagram Fishbone di PT XYZ - Mahesta, Farza; Nugraha, Asep Erik; Nugraha, Billy (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2023)
PT XYZ is a fertilizer production company. Its payroll is managed by the remuneration team, divided into organic and non-organic employees. The role demands precision and timely delivery, leading to high workload-induced stress and reduced productivity. Physical and mental demands, time pressure, performance, effort, and frustration are only few of the variables taken into account in this research using the NASA-TLX approach to evaluate the mental strain of the pay staff. A burden Weighted Load (WWL) score of 76.93 indicates a heavy mental burden was found throughout the examination. The WWL for organic employees surpasses non-organics, with values of 81.3, 94.67, 70.67, 93.3, 94, and 85.3, compared to non-organic employees with scores of 67.3, 74.67, 56, 74.67, 63.3, and 68, respectively. Therefore, it's crucial to propose improvements that normalize the workload, aiming to enhance both well-being and productivity.